Pengembangan Bahan Ajar Handout Berbasis HOTS Tema 9 Kelas 4 SD - Intan Sukengsi; Sugeng Eko Putro Widoyoko; Galih Yansaputra (Dharmas Education Journal (DE_Journal), 2021)
The problem of this study is to overcome the feeling of laziness and boredom felt by students in learning. And less interesting teaching materials that can be learned by students. This study aims at developing HOTS-based handout teaching materials for fourth grade elementary school students on the theme 9 Sub-theme 3 Conservation of Natural Resources Wealth in Indonesia. This study uses a R & D (Research and Development) through 4D model that consisted of the Define, Design, Develop and Disseminate stages adopted from Thiagarajan. Data collection methods used were interviews, validation questionnaires, student response questionnaires, and tests. Methods of data analysis using descriptive analysis. Product validation is based on content feasibility, language, handout display design, compatibility with HOTS, and compatibility with reading skills. Validators consist of academics, practitioners, and students. This development activity obtained the result of the mean final score of meeting 1 obtained 79.28 with criteria B (Good) and meeting 2 obtained better results, namely a mean of 86.42 with criterion A (very good). Thus, the product development of handout teaching materials based on HOTS theme 9 in grade 4 elementary school  is feasible.